Antecedents - Consequences Of Innovation Culture In Family Firms - Antonius Singgih Setiawan; Delfi Panjaitan (Jurnal Manajemen, 2024)
This research aims to see how innovation culture is essential for a business organisation. However, more than a culture of innovation needs to look only at the trigger aspect, it also needs to look at the impact that will be created. Therefore, this research will explain the relationship between entrepreneurs and business characteristics in the context of the ability to see opportunities and improve in creating an innovation culture and the impact of innovation culture on achieving business continuity. Using a sample of 147 (98 per cent) entrepreneur respondents in Palembang, the research hypothesis was tested using structural equation modelling (SEM) and partial least squares (PLS) analysis with Warp PLS version 5.0 software. The results conclude that the entrepreneur's characteristics, the ability to see opportunities, and the ability to improvise positively affect company innovation culture, and innovation culture positively affects business continuity in family firms in Palembang.